Indicators of development in a community / Wan Hanisah Wan Ismail - Wan Ismail, Wan Hanisah (Universiti Teknologi MARA Cawangan Pahang, 1996)
Development has long been associated with an increase in income, the level of poverty and unemployment. However, these three elements are merely the quantitative aspects of development. Robert (1979), however, relates another facet of the outcomes of development to the process of personal and social growth. This includes the creation of new attitude, new resilience and new optimism. This paper describes some of the indicators that explains both the physical and aesthetic aspects of development.